A revised classification of orders and families in the two major subclasses of Lecanoromycetes (Ascomycota) based on a temporal approach. (6th September 2018) - Kraichak, Ekaphan; Huang, Jen-Pan; Nelsen, Matthew; Leavitt, Steven D; Lumbsch, H Thorsten
Abstract: Taxonomic ranks above the species level are inherently arbitrary. However, there is a growing number of publications aimed at more consistent classifications with comparable ranks among taxa. For this study, we use a recently developed temporal approach that utilizes time-calibrated chronograms to identify and define temporal bands for comparable ordinal and family ranks in Lecanoromycetes, the most diverse lineage of lichen-forming fungi. A multi-locus dataset consisting of 539 taxa in the two major subclasses of Lecanoromycetes, Lecanoromycetidae and Ostropomycetidae, was used to address the circumscription of families and orders. Based on the temporal banding approach, clades that share a common ancestor between 176 and 194 Mya and a time window of 111–135 Mya correspond to order-level and family-level, respectively. Most currently accepted orders and families were supported in their current circumscription, but some new taxa are described. Here we propose a revised, temporally based classification for the two subclasses. Specifically, three new orders are proposed: Sporastatiales, Schaereriales and Thelenellales. Arctomiales, Hymeneliales and Trapeliales are synonymized with Baeomycetales. Varicellariaceae are proposed as a new family, and Diploschistaceae and Thelotremataceae are resurrected. Squamarinaceae and Stereocaulaceae are synonymized with Cladoniaceae, Carbonicolaceae are synonymized with Lecanoraceae, Letrouitiaceae are synonymized with Brigantiaeaceae, Lobariaceae and Nephromataceae are synonymized with Peltigeraceae, Thrombiaceae are synonymized with Protothelenellaceae, and Miltideaceae are synonymized with Agyriaceae. This study represents an important step towards more consistent, comparable deeper-level taxonomic rankings in the most diverse lineages of lichen-forming fungi.